The Power of “Not-Yet-Sure” dalam Strategi Perubahan Pendidikan - Dina Martha Tiraswati; Siswantoyo Siswantoyo; Iskandar Iskandar (Annusfy : Journal of Multidisciplinary Research, 2026)
This study aims to systematically examine the Power of "Not-Yet-Sure" paradigm as a strategy for adaptive and sustainable educational change. This study uses a literature review method of 32 reputable academic sources covering educational change theory, complexity theory, educational psychology, adaptive leadership, and change management. The results of the study indicate that uncertainty is an inherent character of educational change and cannot be separated from the nature of the education system as a complex adaptive system. The not-yet-sure paradigm, supported by the concepts of growth mindset and reflective learning, enables individuals and educational institutions to interpret uncertainty as a space for learning and innovation. Furthermore, adaptive and distributed leadership has been shown to play a crucial role in managing uncertainty productively through collective learning and strengthening organizational capacity